Electrochemical Potential Gradient as a Quantitative in Vitro Test Platform for Cellular Oxidative Stress - Carson Bryant; Donald Atha; Vytas Reipa (MDPI AG, 2016)
Oxidative stress in a biological system is often defined as a redox imbalance within cells or groups of cells within an organism. Reductive-oxidative (redox) imbalances in cellular systems have been implicated in several diseases, such as cancer. To better understand the redox environment within cellular systems, it is important to be able to characterize the relationship between the intensity of the oxidative environment, characterized by redox potential, and the biomolecular consequences of oxidative damage. In this study, we show that an in situ electrochemical potential gradient can serve as a tool to simulate exogenous oxidative stress in surface-attached mammalian cells. A culture plate design, which permits direct imaging and analysis of the cell viability, following exposure to a range of solution redox potentials, was developed. The in vitro oxidative stress test vessel consists of a cell growth flask fitted with two platinum electrodes that support a direct current along the flask bottom. The applied potential span and gradient slope can be controlled by adjusting the constant current magnitude across the vessel with spatially localized media potentials measured with a sliding reference electrode. For example, the viability of Chinese Hamster Ovary cells under a gradient of redox potentials indicated that cell death was initiated at approximately 0.4 V vs. standard hydrogen electrode (SHE) media potential and this potential could be modified with antioxidants. This experimental platform may facilitate studies of oxidative stress characteristics on different types of cells by enabling imaging live cell cultures that have been exposed to a gradient of exogenous redox potentials.